Horrid henry's jolly joke book - Simon, Francesca; Ross, Tony (Orion Children's Books London, 2016)
In Horrid Henry's Jolly Joke Book, the mischievous Henry shares a collection of silly jokes, pranks, and humorous stories to make readers laugh. Filled with typical Henry-style cheekiness, the book features his mischievous antics and playful attitude toward family, school, and friends. It's a fun, lighthearted read that invites kids to enjoy the humor in everyday situations.